Mempertimbangkan Kembali Program Eliminasi Malaria 2030 dalam Konteks Indonesia - Kristian Wongso Giamto (Jurnal Kebijakan Kesehatan Indonesia, 2017)
Background: Malaria is one of high burden infectious diseases for tropical-subtropical areas worldwide, such as Indonesia, especially in the eastern Indonesia. Malaria eradication once failed in late 1960s, now re-emerge after a commitment statement of Bill Gates in 2007. Now, Indonesia also targeting malaria elimination in 2030. Objective: To determine the feasibility of Malaria Elimination Program 2030, especially in Indonesia with existing modalities to combat malaria. Methods: This paper uses data, ranging 2000-2016, which selected from MEDLINE journal portal and other sources, which found to be relevant with topics, yet reliable. Results and Discussion: Malaria eradication can not be equalized to smallpox's, which has characteristics those very supportive in putting it to be eradicated (such as no subclinical infection and do not involve vector). Until now, issues of fake antimalarial drugs, forest malaria, financing commitment and healthcare service in rural parts of Indonesia remain unanswered and managed optimally. It also appears that medical advances can not contribute optimally without being supported by strategic policies. Conclusion and Suggestions: With existing modalities and situation, malaria control still difficult to be achieved in Indonesia. This will cause malaria eradication program in 2030 as less realistic target. Malaria eradication as a target may be worth to be reconsidered. Malaria control as target may be a more realistic alternative. More advanced studies regarding obstacles in managing malaria in Indonesia and its solutions are mandatory.